ENUMERASI DAN ANALISIS BAKTERI TANAH DI HUTAN LARANGAN ADAT RUMBIO - Rahmi Fitrah; Mokhammad Irfan; Robbana Saragih (Jurnal Agroteknologi, 2017)
One of indicator of soil fertility is the population level of microbial in the soil. This research aims to determine the number of bacterial populations in the soil on yhe Larangan Adat Rumbi Forest with different levels of depth. This research has been carried out on January-February 2015 in the Laboratory of Pathology, Entomology and Microbiology, Faculty of Agriculture and Animal Sciences of State Islamic University of Sultan Syarif Kasim Riau. The method that was used namely observation method by taking soil samples on the Larangan Adat Rumbio Forest then calculated the number of colonies of bacteria and analyze the morphology of the bacteria that was obtained macroscopically and microscopically. Parameters measured were pH of soil, the population of bacteria, bacterial morphology, gram stain, and bacterial cell shape based on soil depth of 0-10 cm, 11-20 cm, 21-30 cm. Observations carried out two stages macroscopic and microscopic observation. The results showed the soil pH on the Larangan Adat Rumbio Forest was 4,11. Total population of bacteria at depth of 0-10 cm namely 3,0 x 109 CFU, then at a depth of 11-20 cm namely of 2,2 x 109 CFU and at depth of 21-30 cm namely 1,6 x 108 CFU. The Results of purification of culture was obtained six isolat two coccus and four bacil consisting of five gram negative bacteria and one gram positive. Need to do further research on bacteria identification to genus or species level.